RİNİTLİ HASTALARDA CD4 VE CD8 LENFOSİT SUBGRUPLARI VE IgE İLİŞKİSİ - TAHAMİLER, Rauf and ÇANAKÇIOĞLU, Salih and EDİZER, Deniz Tuna (Cerrahpaşa Medical Journal, 2019)
Background and Design.- The level of total immunoglobulin (Ig) E in serum, CD4 and CD8 cell counts and CD4/CD8 ratio were evaluated in patients with allergic rhinitis and non-allergic rhinitis with eosinophilic syndrome (NARES), and the results were compared with those in healthy control group. Materials and Methods.- 20 patients with allergic rhinitis, 20 patients with non-allergic rhinitis were evaluated, and compared with control group of 20 subjects. Skin-prick test, nasal smear, total serum IgE level measurement and CD4 and CD8 subgroup determination in peripheric blood were performed. Results.- Total IgE level was found to be higher in allergic rhinitis group compared with other groups (p<0.05). Although CD4 cell count was higher in allergic rhinitis and NARES groups, this difference did not bear any significance when groups were compared with each other. CD8 cell count showed a meaningful difference only in NARES group compared to control group. In terms of CD4/CD8 ratio, it was found to be higher in both allergic rhinitis and NARES groups than in control group, but no statistical significance was noted. In patients with NARES, a correlation was seen between total IgE and CD4/CD8 ratio, but the does not hold true for allergic rhinitis patients. A strong correlation between CD4 and CD8 with CD4/CD8 was seen in both allergic rhinitis and NARES groups. Conclusion.- As a result, it is concluded that CD4 and CD8 cell counts and CD4/CD8 ratio can not be used in the evaluation of rhinitis patients, and a correlation is not seen between IgE and lymphocyte subgroups.